Dietary supplementation with Macleaya cordata extract alleviates intestinal injury in broiler chickens challenged with lipopolysaccharide by regulating gut microbiota and plasma metabolites - Wang, Xiaohui; Zhang, Tong; Li, Wenli; Zhang, Ming’ai; Zhao, Lianwen; Wang, Nianxue; Zhang, Xiaowen; Zhang, Beibei (Frontiers in Immunology, 2024)
The prevention and mitigation of intestinal immune challenge is crucial for poultry production. This study investigated the effects of dietary Macleaya cordata extract (MCE) supplementation on the prevention of intestinal injury in broiler chickens challenged with lipopolysaccharide (LPS). A total of 256 one-day-old male Arbor Acres broilers were randomly divided into 4 treatment groups using a 2×2 factorial design with 2 MCE supplemental levels (0 and 400 mg/kg) and 2 LPS challenge levels (0 and 1 mg/kg body weight). The experiment lasted for 21 d. The results showed that MCE supplementation increased the average daily feed intake during days 0-14. MCE supplementation and LPS challenge have an interaction on the average daily gain during days 15-21. MCE supplementation significantly alleviated the decreased average daily gain of broiler chickens induced by LPS. MCE supplementation increased the total antioxidant capacity and the activity of catalase and reduced the level of malondialdehyde in jejunal mucosa. MCE addition elevated the villus height and the ratio of villus height to crypt depth of the ileum. MCE supplementation decreased the mRNA expression of proinflammatory cytokines interleukin (IL)-6 and IL-8 in the jejunum. MCE addition mitigated LPSinduced mRNA up-expression of pro-inflammatory factors IL-1β and IL-17 in the jejunum. MCE supplementation increased the abundance of probiotic bacteria (such as Lactobacillus and Blautia) and reduced the abundance of pathogenic bacteria (such as Actinobacteriota, Peptostretococcaceae, and Rhodococcus), leading to alterations in gut microbiota composition. MCE addition altered several metabolic pathways such as Amino acid metabolism, Nucleotide metabolism, Energy metabolism, Carbohydrate metabolism, and Lipid metabolism in broilers. In these pathways, MCE supplementation increased the levels of L-aspartic acid, L-Glutamate, L-serine, etc., and reduced the levels of phosphatidylcholine, phosphatidylethanolamine, thromboxane B2, 13-(S)-HODPE, etc. In conclusion, dietary supplementation of 400 mg/kg MCE effectively improved the growth performance and intestinal function in LPS-challenged broiler chickens, probably due to the modulation of gut microbiota and plasma metabolites.